Isolation, synthesis and complement inhibiting activity of the naturally occurring K-76, its analogues and derivatives - Larghi, Enrique Leandro (2011)
The Complement inhibitor K-76 was isolated from the supernatant of the culture broth of the fungus Stachybotrys complementi, nov. sp. K-76. The natural product is a sesquiterpenic dialdehyde which can be partially oxidized to the monocarboxylic acid derivative (K-76 COOH, MX-1), the sodium salt of which is more soluble and less toxic than the natural product. Both, K-76 and K-76 COOH inhibit Complement activation by the classical and alternative pathways, mainly at the C5 level. Reviewed here are the isolation and total syntheses of the natural product as well as aspects of its Complement inhibitory activity. Approaches to the synthesis of grisan, which bears the BCD skeleton of the natural product, as well as the synthesis of CD-, BCD-and ACD-ring structural analogues of K-76, including the use of natural products as starting materials, and evaluation of their biological activity as Complement inhibitors, are also discussed.